The future of the Hungarian sour cherry growing branch - ApátiF., F.; Gonda, I. (International Journal of Horticultural Science, 2010)
The present study deals with the actual situation of the Hungarian sour cherry production in order to outline the chances of the future and the trends of the development anticipated. The general conclusion accepted that on the long run Hungarian sour cherry production ought to be reorganised. The conditions of keeping the position on the international market are outlined: integration of small farms into large plantations (several times 10 hectares), introduction of mechanical harvest and high (15–20 t/ha) yields. For all that, adequate expertise should be developed on the cooperative farms, where the up to date technology could be applied with innovative initiatives. Small farms (up to 1–2 hectares) and home gardens have no chances to stay on the competitive market. The actual volume of sour cherry of 40–70 thousand tons per year cannot be increased in the future. The sour cherry area was 16 000 ha in 2001, the actual is around 12–13 thousand, and will decline during the following 5 years to less than 10 thousand hectares.